The Cassandra Experience: A Mixed Methods Study on the Intragroup Cognitive Dissonance of Italian Expatriates During the First Wave of COVID-19 - Di Domenico, Rossella; Cannata, Davide; Mancini, Tiziana (Frontiers in Psychology, 2021)
In March 2020, Italy was the first European country to be hit severely by the first wave of Covid-19 and to put in place moderate-high containment measures. 594 Italian expatriates participated in a cross-sectional mixed-methods survey focusing on the period that goes from the beginning of March 2020 to the beginning of April 2020. The survey aimed at describing participants’ experiences of conflicting beliefs and behaviour with the Italian or host country communities using the Intragroup Cognitive Dissonance (ICD) framework. We explored (1) Covid-19 risk perception (assessed for themselves, Italian community and the host country community); (2) Covid-19 risk meta-perception (participants’ belief of the Italian and host country communities risk perceptions); (3) emotions intensity (assessed for themselves); (4) national group identification (assessed for themselves in relation to the Italian and host country communities) before and after the Covid-19 first wave in Italy. An inductive thematic analysis of 3 open-ended questions allowed in-depth understanding of Italian expatriates’ experiences. Results describe participants’ ICD with the Italian or host country communities, expressed as a difference between Covid-19 risk-perception and risk meta-perception. ICD predicts that when a dissonance of beliefs and behavior is experienced within an individual’s group, a shift in identification with another more consonant group will happen, provided identity enhancing strategies with the dissonant group. Our findings showed that when the ICD was experienced with the host country community, this was solved through a disidentification strategy and mediated by negative emotions. Identity enhancing strategies with the host country community were unsuccessfully enacted as described by participants’ qualitative answers referring to episodes of racism, ridicule and to a Cassandra effect: predicting a catastrophic future without being believed. Unexpectedly, participants experiencing an ICD with the Italian community did not enact a disidentification strategy. Increase of virtual contacts, enhanced sense of belonging, a stronger identification baseline and different features of the two ICDs can be responsible for these results. This study sheds light on ICD’s relevance in natural settings and on a larger social scale, during global crisis.